2007
DOI: 10.1292/jvms.69.55
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Comparison of Leucocytozoon spp. from Wild Birds of Japan

Abstract: ABSTRACT. Eight species of Japanese birds were found to be infected with Leucocytozoon species using microscopic analysis. We used PCR and sequence analysis of the mitochondrial cytochrome b gene (cyt b) to compare the genetic background among these detected protozoa species. In 20 individuals of 22 samples, a single amplified band was detected from 6 of 8 bird species; 9 Japanese rock ptarmigans (Lagopus mutus japonicus), 4 large-billed crows (Corvus macrorhynchos), 2 carrion crows (C. corone), 2 scops owls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The reactions using BigDye TM terminator mix (Applied Biosystems, Foster City, California, U.S.A.), were run on an ABI3130 (Applied Biosystems, Foster City, California, U.S.A.) auto sequencer. Phylogenetic analyses of about 478 bp sequences were performed as described previously [34]. Briefly, using the neighbor-joining (NJ) method by PAUP program, the Kimura two-parameter model was utilized to estimate the evolutionary distances.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions using BigDye TM terminator mix (Applied Biosystems, Foster City, California, U.S.A.), were run on an ABI3130 (Applied Biosystems, Foster City, California, U.S.A.) auto sequencer. Phylogenetic analyses of about 478 bp sequences were performed as described previously [34]. Briefly, using the neighbor-joining (NJ) method by PAUP program, the Kimura two-parameter model was utilized to estimate the evolutionary distances.…”
Section: Methodsmentioning
confidence: 99%
“…Following the former studies on the prevalence of avian blood protozoa in Japan [11,25], further molecular biological analyses of avian Plasmodium and Leucocytozoon have been reported on wild birds of Japan, respectively [27,34]. More recently, Murata et al (2008) also showed that avian malaria distributed even in a particularly isolated environment of an oceanic island, Minami Daito Island, Japan [26].…”
mentioning
confidence: 97%
“…and/or Haemoproteus spp., and LcytbF and LcytbR were used for Leucocytozoon spp. [28]. We also used the primer set of HAEMNFI and HAEMNR3 [9] for the first reaction and HAEMF and HAEMR2 [2] for the second to amplify Plasmodium spp.…”
Section: Sample Collection Of Birdsmentioning
confidence: 99%
“…Although at least 35 morphologically defined species have been described to date [ 1 ], molecular studies suggest that the true diversity well exceeds this number e.g. [ 2 4 ]. Several of the molecular lineages have demonstrated that the degree of host-specificity varies; some lineages are found consistently only in one bird species, whereas other lineages develop successfully in a wide range of taxonomically varied hosts [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%